Fog computing-enabled robot simultaneous localization and mapping - Yang YANG; Kai LI; Haidong XU; Huajun WANG; Kunlun WANG; Jian LI; Mingtuo ZHOU (物联网学报)
Robot simultaneous localization and mapping (SLAM) is often required when robots are used to explore prior-unknown environment,e.g.,in rescue scenarios.Fog computing,an emerging computing mode could be used to enable faster,more accurate,speedier,and energy-saved robot SLAM.The framework of fog-enabled robot SLAM addressing was proposed,and challenges it faced were analyzed.Finally,technologies by real implementation of testbed were demonstrated.